Dendritic HMPA as a Promoter for the Mukaiyama Aldol and Allylation Reaction - Mummy, Florian; Haag, Rainer (Synlett, 2012)
We synthesized a hexamethylphosphoramide (HMPA) analogue that was immobilized on hyperbranched polyglycerol (hPG) via a covalent approach. This polymeric analogue (hPG-HMPA) can potentially replace carcinogenic HMPA as a Lewis base additive in many reactions involving trichlorosilyl substrates. We investigated immobilized HMPA in the Mukaiyama aldol and allylation reactions. In most cases, yields and selectivities of supported and nonsupported HMPA were similar. Moreover, in the allylation reaction a positive dendritic effect could be observed, and the loading of HMPA could be lowered with hPG-HMPA to catalytic quantities (0.5 mol%). These results demonstrate that the use of HMPA can be avoided by hPG-HMPA without loss in terms of yield or selectivity.
Keywords: aldol reaction; homogeneous catalysis; supported catalysts; organocatalysis; HMPA; polymeric support